Co-Existence of Two Multidrug-Resistant Non-Fermenter Gram-Negative Bacilli: The Dead End or is There Still Hope? - Preethy Edavaloth; Sahjid Mukhida; Sriram Kannuri; Heer Shah; Amitesh Datta (Medsci Publications, 2023)
NA